Caracterização sócio-econômica de queijarias familiares no Sudoeste do Paraná - Beal, Mariana (2015)
The need to generate income in small spaces territorial challenges farmers around the world, and the small family agricultural industry may be one of the solutions for rural development in Brazil. This research aimed to study the trajectory of six cases of production and marketing of colonial cheese in southwestern Paraná with families of farmers who participated in the social construction of the market. And in every case studied the start of production took place on a small scale and used the learning passed on from previous generations. The activity raised the income of families effectively and improved its clothing and housing conditions, while it gave them personal satisfaction with the craft. Studying these stories helped understand the actions that were instrumental in raising the chances of successful production and marketing of colonial cheeses.